A border surveillance system using WSN under various environment characteristics. (22nd July 2019) - Arfaoui, Imen; Boudriga, Noureddine
Surveillance has become a promising application area of wireless sensor networks (WSNs) where detecting and tracking an intruder as it moves through a sensor network is becoming an increasingly important challenge. This motivates us to investigate the impact of some factors such as the area geography and the intruders behaviours. For this, we present in this paper an efficient surveillance system that uses a WSN deployed inside a border area in order to detect an intruder at least N times from its entrance. The proposed surveillance system is examined under various environment characteristics. First, we focus on modeling the area into multi-thick lines architecture. Then, we provide a deployment method to detect the intruder from its entrance in an area without obstacles. Finally, we investigate the effect of the obstacles in the area and we provide a general surveillance system for detection purpose that considers different intruders behaviours.